Starch-based hard carbon negative electrode material, preparation method thereof and sodium ion battery
By oxidative modification of starch, single crystal particles are generated, the problem of agglomeration and fusion of starch-based hard carbon particles is solved, the physical and chemical properties and sodium storage capacity are significantly improved, and the performance of sodium ion batteries is improved.
Patent Information
- Application Number
- CN202510019748.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
In the prior art, the agglomeration and fusion between starch-based hard carbon particles is serious, resulting in uneven particle size distribution, large D50, low powder compaction, insufficient physical and chemical performance, and insufficient sodium storage capacity and first-term effect.
By oxidative modification of the starch, a single crystal particle can be generated with an angular morphology with a specific angle, avoiding the agglomeration and fusion of particles, improving physical and chemical properties, improving particle size distribution uniformity and compaction, and increasing sodium storage sites.
The physical and chemical properties of starch-based hard carbon negative electrode materials have been significantly improved, the particle size distribution is uniform, the compaction is improved, and the sodium storage capacity and first-term effect are improved.
Smart Images

Figure CN119419266A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a starch-based hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Due to the shortage of lithium resources and the pressure of rising prices, sodium-ion batteries have regained public attention and have shown great application potential in the fields of grid energy storage, low-speed vehicles, etc. For the negative electrode material of sodium-ion batteries, hard carbon is the material most likely to achieve commercial application.
[0003] The advantage of industrial starch as a raw material for hard carbon precursors is that it is a high-purity industrial product, which ensures the consistency and stability of the product. At the same time, the raw material source is abundant, the market supply is sufficient and stable, and the risk of a single supplier is reduced. However, its bottleneck lies in the high difficulty of processing and the tendency to foam and expand during high-temperature carbonization, which limits commercial production and affects performance. Starch is a polysaccharide, a high-molecular carbohydrate formed by the dehydration polymerization of glucose molecules. The glucose molecules are connected by α-1,4 glycosidic bonds or α-1,6 glycosidic bonds. Direct high-temperature carbonization of ordinary starch will cause the starch particles to foam and fuse, because in the carbonization stage, a large amount of H 2 O、CO 2 and CO small molecule gas, a large amount of gas gushed out. Although long-term low-temperature pre-stabilization of starch can achieve starch stabilization and then carbonization, it requires a time-consuming stabilization process (more than 72 hours), which is not conducive to commercial mass production. Moreover, after mass production, due to the problems of uneven temperature and insufficient reaction, the materials after long-term pre-stabilization or the materials modified by other technical means still have the risk of foaming and expansion at the high-temperature carbonization end.
[0004] In addition, the prior art also has the following problems:
[0005] 1) The unmodified starch-based hard carbon particles are seriously agglomerated and fused, which directly leads to problems such as uneven particle size distribution, large D50, and low powder compaction, and the physical and chemical properties do not meet the standards.
[0006] 2) The properties of the hard carbon precursor largely determine the sodium storage capacity of the hard carbon material after high-temperature carbonization. It is difficult to achieve a high-capacity breakthrough in starch-based hard carbon by simply changing the high-temperature carbonization process.
[0007] 3) Low solvent molecules in carbonate electrolyte systems (such as EC: ethylene carbonate) can enter the interior of the carbon layer of incompletely grown hard carbon, resulting in irreversible capacity loss. Because when the diameter of the solvent molecule is smaller than the diameter of the pore opening, the solvent molecule will penetrate into the bulk phase of the material. This makes the actual surface area of the starch-based hard carbon material (also called the "electrolyte accessible surface area") much larger than the surface area of the material, resulting in excessive capacity loss and low initial efficiency.
[0008] Therefore, how to avoid the agglomeration and fusion of starch-based hard carbon particles, improve the physical and chemical properties of starch-based hard carbon negative electrode materials, and increase the sodium storage capacity and initial efficiency is a technical problem that needs to be solved urgently. Summary of the invention
[0009] In view of the deficiencies of the prior art, the object of the present invention is to provide a starch-based hard carbon negative electrode material and a preparation method thereof and a sodium ion battery. The single crystal particles in the starch-based hard carbon negative electrode material provided by the present invention have regular morphology and angular morphology at specific angles, which can avoid the phenomenon of particle agglomeration and fusion, and the physical and chemical properties of the starch-based hard carbon negative electrode material are significantly improved, the particle size distribution is uniform and the compaction is improved, and the sodium storage sites are also increased, which is conducive to the improvement of sodium storage capacity and first efficiency.
[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, wherein the single crystal particles have an angular morphology, and the edge angle is 90°-130°.
[0012] It should be noted that the angularity of particles is an important indicator used to describe the shape characteristics of particles. The angularity refers to the sharpness of the edges and corners of particles. The angularity of particles can be described quantitatively or qualitatively in a variety of ways. For example, the angularity can be evaluated by measuring the angle at the corners of particles, observing the contour shape of particles under a microscope, etc.
[0013] The single crystal particles in the starch-based hard carbon negative electrode material provided by the present invention have regular morphology and angular morphology with specific angles, which can avoid the phenomenon of particle agglomeration and fusion. In addition, the physical and chemical properties of the starch-based hard carbon negative electrode material are significantly improved, the particle size distribution is uniform and the compaction is improved, and the sodium storage sites are also increased, which is beneficial to the improvement of sodium storage capacity and first efficiency.
[0014] In the present invention, the single crystal particles have an angular morphology and are polygonal, with an angle of 90°-130°, for example, 90°, 100°, 110°, 120° or 130°, etc. This morphology helps the packing density and stability of the hard carbon single crystal particles in the electrode material, thereby improving the energy density and cycle performance of the battery. At the same time, this angular morphology can also effectively reduce the agglomeration of particles during the charge and discharge process.
[0015] Preferably, the particle size D50 of the single crystal particles is 5-15μm, for example, it can be 5μm, 7μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, and 80% of the single crystal particles are distributed in the range of 3-30μm, for example, it can be 3μm, 5μm, 10μm, 15μm, 20μm, 25μm or 30μm, etc.
[0016] In the present invention, the particle size distribution of the single crystal particles in the starch-based hard carbon negative electrode material is uniform, which is conducive to the embedding and de-embedding of sodium ions, shortens the diffusion path of sodium ions, reduces the diffusion resistance, and thus improves the charge and discharge performance of the battery. In addition, the negative electrode material with uniform particle size distribution is conducive to improving the viscosity and stability of the slurry, reducing the difficulty of coating, and thus optimizing the production process of the battery.
[0017] It should be noted that 80% of the single crystal particles are distributed in the range of 3-30 μm, which means that the particle size range corresponding to the cumulative distribution percentage from 10% to 90% from small to large, that is, the interval range of D90~D10 is 3-30 μm.
[0018] Preferably, the single crystal dispersion rate of the single crystal particles is ≥90%, for example, it may be 90%, 92%, 94%, 96%, 98% or 99%.
[0019] It should be noted that the single crystal dispersion rate refers to the ratio of the number of individually dispersed single crystal particles to the total number of particles in a given system. It reflects the degree to which the single crystal particles avoid agglomeration and are evenly distributed in the system.
[0020] In the present invention, the single crystal dispersion rate of the single crystal particles is ≥90%, which helps to reduce the agglomeration phenomenon between the particles, making the electrode material more uniform and stable, thereby reducing polarization and improving the overall performance of the battery.
[0021] Preferably, the starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.38-0.4 nm, for example, it can be 0.38 nm, 0.39 nm or 0.4 nm.
[0022] It should be noted that the preparation of starch-based hard carbon materials usually undergoes a high-temperature carbonization step. When the temperature rises to a certain level, the carbon chains in the starch molecules begin to undergo violent pyrolysis, rearrangement and polycondensation reactions. Although the final hard carbon material has an overall disordered structure, there are still some locally oriented, graphite-like small-sized stacks of hexagonal carbon atoms. These stacks are usually only a few nanometers thick and have a limited number of stacked layers, forming graphite-like microcrystalline regions. The graphite-like microcrystalline region can be characterized by XRD or high-resolution transmission electron microscopy. For example, the d (002) value in the XRD test can characterize the average carbon interlayer spacing of the graphite-like microcrystalline region. The value in the range of 0.38-0.40 is conducive to the deintercalation of sodium ions and improves the kinetic properties of the hard carbon material.
[0023] Preferably, the BET of the starch-based hard carbon negative electrode material is 0.1-5 m 2 / g, for example, it can be 0.1m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g or 5m 2 / g, etc.
[0024] In the present invention, the BET of the starch-based hard carbon negative electrode material is 0.1-5m 2 / g, the BET value is small, which proves that closed cells are effectively generated, which helps to improve the first efficiency, corresponding to the high first efficiency of ≥90%.
[0025] Preferably, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1 t is greater than 0.9 g / cm 3 , for example, it can be 0.91 g / cm 3 , 0.93g / cm 3 , 0.95g / cm 3 , 0.97g / cm 3 , 0.99g / cm 3 or 1.1 g / cm 3 etc., preferably 0.95-1.1 g / cm 3 .
[0026] In the present invention, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1 t is greater than 0.9 g / cm 3 , which helps to improve the energy density of the battery.
[0027] Preferably, the starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.06-0.2 cm 3 / g, for example, 0.06 cm 3 / g, 0.10cm 3 / g, 0.14cm 3 / g, 0.18cm 3 / g or 0.2cm 3 / g, etc., the pore size of the closed pore is <0.4nm, for example, it can be 0.3nm, 0.2nm or 0.1nm, etc.
[0028] It should be noted that the volume of closed pores can be calculated according to the formula: closed pore volume = 1 / true density - 1 / 2.26; the true density is directly tested by a true density meter, which refers to the actual mass of solid per unit volume when the material is in an absolutely dense state. It can be used to analyze parameters such as closed pores in the material. The BSD-TD-K fully automatic true density and porosity analyzer produced by Best Instrument Technology Co., Ltd. is used. During the test, the powder can be directly loaded into the sample test cavity.
[0029] It should be noted that the pore size of the closed pore is smaller than the solvent molecules and solvated Na + The size of the pores is also called the pore diameter <0.4nm, which is conducive to the storage of sodium ions and hinders the entry of solvent molecules. This protects the active sites in the pores that can store sodium to a certain extent, avoiding excessive capacity loss, thereby improving the first efficiency and being suitable for low-molecular solvent electrolytes. It is worth noting that the nitrogen adsorption value in the table test can characterize the size of the pore diameter. When the pore diameter of the material is smaller than the diameter of the nitrogen molecule (approximately 0.364nm), the nitrogen molecules cannot enter the pores, the adsorption amount is close to 0, and the BET value is also close to 0, that is, the smaller the BET value, the smaller the pore diameter, and the closer it is to the diameter of the nitrogen molecule. Therefore, based on the starch-based hard carbon negative electrode material BET <1m 2 / g, the first efficiency is >90%, indicating that the pore diameter can effectively prevent nitrogen molecules from entering and solvent molecules from entering the pores. Therefore, BET <1m 2 / g and the first efficiency is greater than 90%, the pore diameter is less than 0.4nm.
[0030] In a second aspect, the present invention provides a method for preparing the starch-based hard carbon negative electrode material as described in the first aspect, the preparation method comprising the following steps:
[0031] The oxidant and starch are mixed to carry out an oxidation reaction to obtain oxidized modified starch.
[0032] The oxidatively modified starch is subjected to low-temperature pretreatment and high-temperature carbonization treatment in sequence to obtain the starch-based hard carbon negative electrode material.
[0033] In the preparation method provided by the present invention, starch is oxidatively modified, which solves the problem of difficulty in starch processing; oxygen-containing functional groups are grafted on the surface of the oxidatively modified starch, and the oxygen-containing functional groups and starch molecules are fully cross-linked with each other, which is beneficial to inhibiting the growth of graphite crystallites during the subsequent high-temperature carbonization process, inhibiting graphitization, generating more disordered carbon structures, and increasing sodium storage sites, thereby facilitating the improvement of sodium storage capacity and the first efficiency, and being suitable for low-molecular solvent electrolytes.
[0034] In the preparation method provided by the present invention, starch is oxidatively modified to release part of the water and small molecules contained in the starch, which plays a stabilizing role, greatly reduces the time cost of low-temperature pretreatment, shortens the production cycle, and is conducive to commercial production.
[0035] Preferably, the viscosity of the oxidized modified starch is 6-14 mPa·s, for example, 6 mPa·s, 8 mPa·s, 10 mPa·s, 12 mPa·s or 14 mPa·s.
[0036] In the present invention, the viscosity of the oxidized modified starch is used to characterize the oxidation degree of the oxidized modified starch. The oxidation degree of the oxidized starch is significantly negatively correlated with the viscosity. A viscosity of 6-14 mPa·s indicates a decrease in viscosity. After the starch is oxidized, the content of oxygen-containing functional groups is increased.
[0037] Preferably, the crystallinity of the oxidized modified starch is 8-20%, for example, 8%, 10%, 12%, 14%, 16%, 18% or 20%.
[0038] In the present invention, the crystallinity of the oxidized modified starch is used to characterize the oxidation degree of the oxidized modified starch. A crystallinity of 8-20% indicates that the crystallinity is reduced, and the oxidation degree of the starch is increased by the oxidation process.
[0039] Preferably, the oxidatively modified starch contains oxygen-containing functional groups, and the oxygen-containing functional groups include carboxyl groups.
[0040] In the present invention, the oxygen-containing functional groups and starch molecules are more fully cross-linked with each other, thereby hindering the growth of graphite crystallites in the subsequent high-temperature carbonization process, inhibiting graphitization, generating more disordered carbon structures, and increasing sodium storage sites, which is beneficial to the improvement of sodium storage capacity. In addition, the oxygen-containing functional groups can generate volatile components of carbon monoxide and carbon dioxide. The growth of the carbon layer will cause the holes left by the overflow of gas molecules to be transformed from open holes to nano-closed-cell structures during the high-temperature carbonization process, which is beneficial to the storage of sodium ions therein and hindering the entry of solvent molecules. This protects the active sites in the pores that can store sodium to a certain extent, avoiding excessive capacity loss, thereby improving the first effect, and is suitable for low-molecular solvent electrolytes.
[0041] Preferably, the oxygen-containing functional groups in the oxidatively modified starch further include any one of carbonyl, hydroxyl or quinone groups, or a combination of at least two of them.
[0042] In the present invention, the carbonyl and carboxyl groups are stable functional groups during the low-temperature pretreatment process, which can synergistically construct a stable cross-linked structure and promote the disordering of the carbon structure. In addition, the small gas molecules (such as CO 2 and CO, etc.) will further change the microstructure of carbon materials and play a dual regulatory role.
[0043] Preferably, the mass content of oxygen-containing functional groups in the oxidized modified starch is 0.05-0.8%, for example, it can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%.
[0044] In the present invention, the mass content of oxygen-containing functional groups in the oxidized modified starch is used to characterize the oxidation degree of the oxidized modified starch. A mass content of 0.05-0.8% helps to fully inhibit graphitization, generate more disordered carbon structures, and increase sodium storage sites, which is beneficial to the improvement of sodium storage capacity and the first efficiency, and is suitable for low-molecular solvent electrolytes. In addition, it can fully release part of the water and small molecules contained in the starch, play a stabilizing role, and is beneficial to commercial production.
[0045] Preferably, the oxidant includes any one of hydrogen peroxide, sodium hypochlorite, potassium permanganate, chlorate or ammonium persulfate, or a combination of at least two thereof. Exemplarily, the chlorate may be sodium chlorate or potassium chlorate.
[0046] Preferably, the starch comprises any one of corn starch, wheat starch, rice starch, tapioca starch or sweet potato starch, or a combination of at least two thereof.
[0047] Preferably, the specific steps of mixing include:
[0048] The starch and the solvent are mixed to obtain a starch emulsion solution, and then a pH adjuster is added to adjust the pH, followed by the addition of an oxidant.
[0049] In the present invention, liquid phase oxidation modification of starch can increase the oxidation degree of starch and make the oxidation uniform.
[0050] Preferably, the solvent includes water, for example, distilled water.
[0051] Preferably, the mass concentration of the starch milk solution is 20-50%, for example, it can be 20%, 30%, 40% or 50%.
[0052] Preferably, the pH adjuster comprises sodium hydroxide solution.
[0053] In the present invention, the purpose of adjusting pH is: 1) affecting the oxidation rate: no matter what kind of oxidant is used, its oxidation rate is related to the pH value of the reaction medium; 2) affecting the degree of oxidation: when the pH value changes from low to high, the content of oxygen-containing functional groups gradually increases, affecting the degree of oxidation of starch.
[0054] Preferably, the mass volume ratio concentration of the oxidant is 1-20 g / L, for example, it can be 1 g / L, 5 g / L, 10 g / L, 15 g / L or 20 g / L.
[0055] Preferably, the mass ratio of the starch to the oxidant is 1:(0.002-0.04), for example, it can be 1:0.002, 1:0.005, 1:0.01, 1:0.02, 1:0.03 or 1:0.04, etc.
[0056] In the present invention, a suitable mass ratio of starch and oxidant is helpful to controllably adjust the degree of oxidation, while too little or too much will affect the material properties.
[0057] Preferably, the temperature of the oxidation reaction is 30-50°C, for example, 30°C, 40°C or 50°C.
[0058] Preferably, the temperature of the low-temperature pretreatment is 150-350°C, for example, it can be 150°C, 200°C, 250°C, 300°C or 350°C.
[0059] Preferably, the low-temperature pretreatment time is 6-48 h, for example, it can be 6 h, 12 h, 18 h, 24 h, 30 h, 36 h, 42 h or 48 h.
[0060] In the present invention, the time cost of low-temperature pretreatment is greatly reduced, which is of great significance.
[0061] Preferably, the temperature of the high temperature carbonization treatment is 1300-1600°C, for example, it can be 1300°C, 1400°C, 1500°C or 1600°C.
[0062] Preferably, the high temperature carbonization treatment time is 4-10 h, for example, 4 h, 6 h, 8 h or 10 h.
[0063] Preferably, the preparation method comprises the following steps:
[0064] (1) Starch and a solvent are mixed to obtain a starch emulsion solution with a mass concentration of 20-50%, and then a pH adjuster is added to adjust the pH value to 6-9 (for example, 6, 7, 8 or 9, etc.), and then an oxidant with a mass volume ratio concentration of 1-20 g / L is added, and an oxidation reaction is carried out under stirring conditions to obtain oxidized modified starch.
[0065] The viscosity of the oxidized modified starch is 6-14 mPa·s, the crystallinity is 8-20%, and the moisture content is ≤11% (for example, it can be 11%, 10%, 8%, 6% or 4%, etc.); the oxidized modified starch contains oxygen-containing functional groups, the oxygen-containing functional groups include carboxyl groups, and the mass content of oxygen-containing functional groups in the oxidized modified starch is 0.05-0.8%; the mass ratio of the starch to the oxidant is 1:(0.002-0.04); the temperature of the oxidation reaction is 30-50°C, and the time is 0.5-3h.
[0066] (2) In an air atmosphere, the temperature is raised to 150-350°C at a heating rate of 1-5°C / min (for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc.), and the oxidized modified starch is subjected to a low-temperature pretreatment for 6-48 hours. Then, in a protective atmosphere (for example, a nitrogen atmosphere), the temperature is raised to 1300-1600°C at a heating rate of 1-10°C / min (for example, 1°C / min, 3°C / min, 5°C / min, 7°C / min or 9°C / min, etc.), and a high-temperature carbonization treatment is performed for 4-10 hours. After the treatment, the temperature is lowered, and the mixture is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0067] In a third aspect, the present invention provides a sodium ion battery, wherein the negative electrode plate of the sodium ion battery comprises the starch-based hard carbon negative electrode material as described in the first aspect.
[0068] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] (1) The single crystal particles in the starch-based hard carbon negative electrode material provided by the present invention have regular morphology and angular morphology with specific angles, which can avoid the phenomenon of particle agglomeration and fusion. In addition, the physical and chemical properties of the starch-based hard carbon negative electrode material are significantly improved, the particle size distribution is uniform and the compaction is improved, and the sodium storage sites are also increased, which is beneficial to the improvement of sodium storage capacity and first efficiency.
[0071] (2) In the preparation method provided by the present invention, starch is oxidatively modified, which solves the problem of difficulty in starch processing. The surface of the oxidatively modified starch is grafted with oxygen-containing functional groups, and the oxygen-containing functional groups and starch molecules are fully cross-linked with each other, which is beneficial to inhibit the growth of graphite crystallites in the subsequent high-temperature carbonization process, inhibit graphitization, generate more disordered carbon structures, and increase sodium storage sites, which is beneficial to the improvement of sodium storage capacity and the improvement of the first efficiency, and is suitable for low-molecular solvent electrolytes.
[0072] (3) In the preparation method provided by the present invention, the starch is oxidatively modified, which releases part of the water and small molecules contained in the starch, plays a stabilizing role, greatly reduces the time cost of low-temperature pretreatment, shortens the production cycle, and is conducive to commercial production.
[0073] (4) The reversible capacity of the starch-based hard carbon negative electrode material provided by the present invention can reach 335 mAh / g, and the first-cycle coulombic efficiency can reach 91.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is a SEM image of the starch-based hard carbon negative electrode material provided in Example 7 of the present invention at 1K magnification.
[0075] Figure 2 This is a SEM image of the starch-based hard carbon negative electrode material provided in Example 7 of the present invention at a magnification of 5K.
[0076] Figure 3 This is a SEM image of the starch-based hard carbon negative electrode material provided in Example 7 of the present invention at a magnification of 2K.
[0077] Figure 4 This is the charge and discharge curve of the starch-based hard carbon negative electrode material provided in Example 7 of the present invention.
[0078] Figure 5 Particle size distribution curve of the starch-based hard carbon negative electrode material provided in Example 7 of the present invention.
[0079] Figure 6 This is a SEM image of the starch-based hard carbon negative electrode material provided in Comparative Example 2 of the present invention at a magnification of 2K.
[0080] Figure 7 This is the charge and discharge curve of the starch-based hard carbon negative electrode material provided in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] Example 1
[0083] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, and the single crystal particles have an angular morphology, and the edge angle is 110°.
[0084] The particle size D50 of the single crystal particles is 10 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 99%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.39 nm.
[0085] The BET of the starch-based hard carbon negative electrode material is 2.3 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.94g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.068 cm 3 / g.
[0086] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0087] (1) Wheat starch and distilled water are mixed to obtain a starch emulsion solution with a mass concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3 g / L is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0088] The viscosity of the oxidized modified starch is 6 mPa·s, the crystallinity is 10%, and the water content is 5%. The oxidized modified starch contains carboxyl groups, and the mass content of carboxyl groups in the oxidized modified starch is 0.52%. The mass ratio of wheat starch to sodium hypochlorite is 1:0.02. The temperature of the oxidation reaction is 35° C., and the time is 3 hours.
[0089] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1300°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0090] Example 2
[0091] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, and the single crystal particles have an angular morphology, and the edge angle is 100°.
[0092] The particle size D50 of the single crystal particles is 12 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 93%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.393 nm.
[0093] The BET of the starch-based hard carbon negative electrode material is 3.2 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.95g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.062 cm 3 / g.
[0094] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0095] (1) Cassava starch and distilled water are mixed to obtain a starch milk solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0096] The viscosity of the oxidized modified starch is 10 mPa·s, the crystallinity is 12%, and the water content is 8%. The oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.37%. The mass ratio of the cassava starch to sodium hypochlorite is 1:0.01. The temperature of the oxidation reaction is 35° C., and the time is 3 hours.
[0097] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1300°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0098] Example 3
[0099] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, and the single crystal particles have an angular morphology, and the edge angle is 110°.
[0100] The particle size D50 of the single crystal particles is 12 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 95%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.392 nm.
[0101] The BET of the starch-based hard carbon negative electrode material is 3.3 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.95g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.07 cm 3 / g.
[0102] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0103] (1) Corn starch and distilled water are mixed to obtain a starch emulsion solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0104] The viscosity of the oxidized modified starch is 7 mPa·s, the crystallinity is 11%, and the water content is 8%. The oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.49%. The mass ratio of the corn starch to sodium hypochlorite is 1:0.03. The temperature of the oxidation reaction is 35° C., and the time is 3 hours.
[0105] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1300°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0106] Example 4
[0107] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, and the single crystal particles have an angular morphology, and the edge angle is 90°.
[0108] The particle size D50 of the single crystal particles is 10 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 96%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.398 nm.
[0109] The BET of the starch-based hard carbon negative electrode material is 2.0 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.96g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.0935 cm 3 / g.
[0110] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0111] (1) Corn starch and distilled water are mixed to obtain a starch emulsion solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0112] The viscosity of the oxidized modified starch is 11 mPa·s, the crystallinity is 15%, and the water content is 2%; the oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.38%; the mass ratio of the corn starch to sodium hypochlorite is 1:0.04; the temperature of the oxidation reaction is 35° C., and the time is 2 hours.
[0113] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1300°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0114] Example 5
[0115] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, wherein the single crystal particles have an angular morphology, and the angular angle is 130°.
[0116] The particle size D50 of the single crystal particles is 13 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 98%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.389 nm.
[0117] The BET of the starch-based hard carbon negative electrode material is 2.3 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.93g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.0712 cm 3 / g.
[0118] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0119] (1) Corn starch and distilled water are mixed to obtain a starch emulsion solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0120] The viscosity of the oxidized modified starch is 14 mPa·s, the crystallinity is 18%, and the water content is 5%. The oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.21%. The mass ratio of the corn starch to sodium hypochlorite is 1:0.04. The temperature of the oxidation reaction is 35° C., and the time is 1 hour.
[0121] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1300°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0122] Example 6
[0123] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, wherein the single crystal particles have an angular morphology, and the angular angle is 120°.
[0124] The particle size D50 of the single crystal particles is 9 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 90%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.387 nm.
[0125] The BET of the starch-based hard carbon negative electrode material is 0.8 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.97g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.1304 cm 3 / g, the pore size of the closed pore is less than 0.4nm.
[0126] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0127] (1) Corn starch and distilled water are mixed to obtain a starch emulsion solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0128] The viscosity of the oxidized modified starch is 11 mPa·s, the crystallinity is 15%, and the water content is 5%. The oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.38%. The mass ratio of the corn starch to sodium hypochlorite is 1:0.02. The temperature of the oxidation reaction is 35° C., and the time is 2 hours.
[0129] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1400°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0130] Example 7
[0131] The present embodiment provides a starch-based hard carbon negative electrode material, wherein the starch-based hard carbon negative electrode material comprises single crystal particles, wherein the single crystal particles have an angular morphology, and the angular angle is 120°.
[0132] The particle size D50 of the single crystal particles is 8 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm. The single crystal dispersion rate of the single crystal particles is 97%. The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.381 nm.
[0133] The BET of the starch-based hard carbon negative electrode material is 0.4 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.99g / cm 3 The starch-based hard carbon negative electrode material has closed pores with a closed pore volume of 0.181 cm 3 / g, the pore size of the closed pore is less than 0.4nm.
[0134] This embodiment also provides a method for preparing the above-mentioned starch-based hard carbon negative electrode material, the preparation method comprising the following steps:
[0135] (1) Corn starch and distilled water are mixed to obtain a starch emulsion solution with a concentration of 30%, and then a sodium hydroxide solution with a concentration of 3 wt % is added to adjust the pH value to 9. Subsequently, sodium hypochlorite with a mass volume ratio of 3% is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch, which is then centrifuged and washed.
[0136] The viscosity of the oxidized modified starch is 11 mPa·s, the crystallinity is 15%, and the water content is 4%. The oxidized modified starch contains carboxyl groups, and the mass content of the carboxyl groups in the oxidized modified starch is 0.38%. The mass ratio of the corn starch to sodium hypochlorite is 1:0.035. The temperature of the oxidation reaction is 35° C., and the time is 2 hours.
[0137] (2) In a medium-temperature furnace in an air atmosphere, the temperature is raised to 200°C at a heating rate of 3°C / min, the oxidized modified starch is subjected to low-temperature pretreatment for 10 hours, and then the temperature is reduced to below 50°C, and a sample is taken to obtain a low-temperature pretreated material, which is then transferred to a high-temperature furnace in a nitrogen atmosphere, and the temperature is increased to 1500°C at a heating rate of 2°C / min for a high-temperature carbonization treatment for 4 hours. After the treatment, the temperature is reduced to below 50°C for sampling, and then the sample is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
[0138] Figure 1 , Figure 2 and Figure 3 The SEM images of the starch-based hard carbon negative electrode material provided in this embodiment at different magnifications are shown respectively. It can be seen from the figure that the starch-based hard carbon negative electrode material has no obvious particle agglomeration, the particle dispersion is high, and the single crystal particles have an angular morphology with an edge angle of 120° and a D50 of 8μm.
[0139] Figure 4The charge and discharge curve of the starch-based hard carbon negative electrode material provided in this embodiment is shown. It can be seen from the figure that at a current density of 0.1C, the reversible specific capacity of the starch-based hard carbon negative electrode material can reach 335.8mAh / g, and the first-cycle coulombic efficiency is 91.2%, with significant performance improvement.
[0140] Figure 5 The particle size distribution curve of the starch-based hard carbon negative electrode material provided in this embodiment is shown. As can be seen from the figure, the particle size distribution in the starch-based hard carbon negative electrode material is uniform, and there are no agglomerated large particles, which helps to improve compaction.
[0141] Example 8
[0142] The difference between this embodiment and embodiment 1 is that the sodium hypochlorite in step (1) is replaced by a combination of hydrogen peroxide and ammonium persulfate, so that the oxidized modified starch contains carboxyl and carbonyl groups, and the mass content of carboxyl and carbonyl groups is 0.45%.
[0143] The rest of the preparation methods and parameters were the same as those in Example 1.
[0144] Example 9
[0145] The difference between this embodiment and embodiment 1 is that by reducing the temperature of the high-temperature carbonization treatment in step (2), the pore diameter of the closed pores in the starch-based hard carbon negative electrode material is greater than 0.4 nm.
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Example 10
[0148] The difference between this embodiment and embodiment 1 is that the mass ratio of the wheat starch and sodium hypochlorite in step (1) is adjusted so that the mass content of carboxyl groups in the oxidized modified starch is 0.02%.
[0149] The rest of the preparation methods and parameters were the same as those in Example 1.
[0150] Embodiment 11
[0151] The difference between this embodiment and embodiment 1 is that the mass ratio of the wheat starch and sodium hypochlorite in step (1) is adjusted so that the mass content of carboxyl groups in the oxidized modified starch is 1%.
[0152] The rest of the preparation methods and parameters were the same as those in Example 1.
[0153] Example 12
[0154] The difference between this embodiment and embodiment 1 is that in step (1), no sodium hydroxide solution is added for pH adjustment.
[0155] The rest of the preparation methods and parameters were the same as those in Example 1.
[0156] Embodiment 13
[0157] The difference between this embodiment and embodiment 1 is that the temperature of the oxidation reaction in step (1) is 25°C.
[0158] The rest of the preparation methods and parameters were the same as those in Example 1.
[0159] Embodiment 14
[0160] The difference between this embodiment and embodiment 1 is that the temperature of the oxidation reaction in step (1) is 60°C.
[0161] The rest of the preparation methods and parameters were the same as those in Example 1.
[0162] Comparative Example 1
[0163] The difference between this comparative example and Example 1 is that step (1) is not performed, and the time of low-temperature pretreatment in step (2) is 72 hours.
[0164] The starch-based hard carbon negative electrode material provided in this comparative example does not contain single crystal particles.
[0165] The BET of the starch-based hard carbon negative electrode material is 8.9 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.86g / cm 3 The closed pore volume of the starch-based hard carbon negative electrode material is small, which is 0.021cm 3 / g, and the pore diameter of the closed pore is 0.5nm.
[0166] The rest of the preparation methods and parameters were the same as those in Example 1.
[0167] Comparative Example 2
[0168] The difference between this comparative example and Example 7 is that step (1) is not performed, and the time for low-temperature pretreatment in step (2) is 72 hours.
[0169] The starch-based hard carbon negative electrode material provided in this comparative example has serious particle agglomeration and fusion, the proportion of single crystal particles is extremely low, and the particle size D50 of the material is 16.8 μm.
[0170] The BET of the starch-based hard carbon negative electrode material is 2.89 m 2 / g, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1t is 0.88 / cm 3 The closed pore volume of the starch-based hard carbon negative electrode material is small, which is 0.043 cm 3 / g, and the pore diameter of the closed pore is 0.43nm.
[0171] The rest of the preparation methods and parameters were the same as those in Example 7.
[0172] Figure 6 The SEM image of the starch-based hard carbon negative electrode material provided in this comparative example at 2K magnification is shown. It can be seen from the image that the particles in the starch-based hard carbon negative electrode material are severely agglomerated.
[0173] Figure 7 The charge and discharge curve of the starch-based hard carbon negative electrode material provided in this comparative example is shown. It can be seen from the figure that at a current density of 0.1C, the reversible capacity of the starch-based hard carbon negative electrode material is only 296mAh / g, and the first-cycle coulombic efficiency is 87.5%.
[0174] Performance Testing
[0175] The starch-based hard carbon negative electrode materials provided in the above embodiments and comparative examples are prepared into a sodium ion battery, and the specific steps include:
[0176] The starch-based hard carbon negative electrode material is mixed with conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 8:1:1, ground and coated on copper foil, and then dried, rolled and punched to obtain a negative electrode sheet. In an argon glove box, a sodium sheet is used as a counter electrode, a glass fiber membrane is used as a diaphragm, and a 1.5 mol / L electrolyte (the solvent is NaPF 6 , the solvent includes ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:2:2) and assembled into a standard CR2032 button cell.
[0177] The reversible specific capacity and first efficiency tests were performed on the above sodium ion battery, and the test conditions were: test voltage range 0-2V, test at 0.1C current density.
[0178] The test results are shown in Table 1.
[0179] Table 1
[0180]
[0181] analyze:
[0182] It can be seen from the above table that the measured reversible capacity of the starch-based hard carbon negative electrode materials prepared in Comparative Examples 1 and 2 is difficult to exceed 300 mAh / g, the particles are severely agglomerated, the particle size is too large, and the powder compaction is also low. There are problems such as difficulty in improving the capacity, low initial efficiency, and substandard physical and chemical properties. Examples 1-7 that have undergone an oxidation process not only reduce the time cost of low-temperature pretreatment, but also effectively improve the sodium storage capacity, initial efficiency and physical and chemical properties.
[0183] From the comparative analysis of Examples 1, 3-5 and Examples 10-11, it can be seen that the higher the degree of oxidation, the better the battery performance. As the oxidation time increases, the carboxyl content does increase, which promotes the full cross-linking between the carboxyl groups and the starch molecules, helps to increase the sodium storage capacity and promote the formation of closed-cell structure. However, when the degree of oxidation is too high, the situation becomes complicated. On the one hand, the degree of breakage of the starch molecular chain increases, resulting in a decrease in molecular weight; on the other hand, the oxidant can penetrate into the crystalline area of the starch and react. This process destroys the originally dense crystalline structure, making it loose, thereby reducing the relative crystallinity. This structural change, in turn, reduces the degree of cross-linking between the molecular chains, which has an adverse effect on battery performance. Therefore, in order to maximize battery performance, the degree of oxidation must be precisely controlled during the oxidation modification process of starch.
[0184] It can be seen from Example 1 and Example 8 that if carboxyl groups and carbonyl groups are grafted onto starch for modification, it is beneficial to construct a stable cross-linked structure and promote the disordering of the carbon structure.
[0185] It can be seen from Examples 1 and 9 that if the pore size of the closed pores in the starch-based hard carbon negative electrode material is greater than 0.4 nm, it is not conducive to preventing the entry of solvent molecules, resulting in excessive capacity loss, thereby reducing the first efficiency and being unsuitable for low-molecular solvent electrolytes.
[0186] It can be seen from Example 1 and Example 12 that if no sodium hydroxide solution is added in step (1) to adjust the pH, it is not conducive to the oxidation reaction and affects the oxidation efficiency.
[0187] It can be seen from Examples 1 and 13-14 that if the temperature of the oxidation reaction is too low, the relative movement of molecules in the reaction system is too slow, and the probability of starch molecules contacting and reacting with the oxidant is low, so less carboxyl groups are generated and the oxidation degree is too low; if the temperature of the oxidation reaction is too high, part of the oxidized starch will be degraded and dissolved in water, and will be washed away during washing after the reaction is completed, which will also lead to a decrease in the carboxyl content.
[0188] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A starch-based hard carbon negative electrode material, characterized in that: The starch-based hard carbon negative electrode material comprises single crystal particles, and the single crystal particles comprise polygonal particles with an angular morphology, wherein the angular angle is 90°-130°.
2. The starch-based hard carbon negative electrode material according to claim 1, characterized in that: The particle size D50 of the single crystal particles is 5-15 μm, and 80% of the single crystal particles are distributed in the range of 3-30 μm; And / or, the single crystal dispersion rate of the single crystal particles is ≥90%.
3. The starch-based hard carbon negative electrode material according to claim 1, characterized in that: The starch-based hard carbon negative electrode material has a graphite-like microcrystalline region, and the average carbon layer spacing in the graphite-like microcrystalline region is 0.38-0.4nm; And / or, the BET of the starch-based hard carbon negative electrode material is 0.1-5m 2 / g; And / or, the compaction density of the starch-based hard carbon negative electrode material under a pressure of 1 t is greater than 0.9 g / cm 3 .
4. The starch-based hard carbon negative electrode material according to claim 1, characterized in that: The starch-based hard carbon negative electrode material has closed pores, and the volume of the closed pores is 0.06-0.2 cm 3 / g, the pore diameter of closed pores is <0.4nm.
5. A method for preparing a starch-based hard carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The oxidant and starch are mixed to carry out an oxidation reaction to obtain oxidized modified starch; The oxidatively modified starch is subjected to low-temperature pretreatment and high-temperature carbonization treatment in sequence to obtain the starch-based hard carbon negative electrode material.
6. The preparation method according to claim 5, characterized in that: The viscosity of the oxidized modified starch is 6-14 mPa·s; And / or, the crystallinity of the oxidized modified starch is 8-20%.
7. The preparation method according to claim 5, characterized in that: The oxidatively modified starch contains oxygen-containing functional groups, and the oxygen-containing functional groups include carboxyl groups; And / or, the oxygen-containing functional groups in the oxidatively modified starch further include any one or a combination of at least two of a carbonyl group, a hydroxyl group or a quinone group; And / or, the mass content of oxygen-containing functional groups in the oxidized modified starch is 0.05-0.8%.
8. The preparation method according to claim 5, characterized in that: The oxidant comprises any one of hydrogen peroxide, sodium hypochlorite, potassium permanganate, chlorate or ammonium persulfate, or a combination of at least two thereof; And / or, the starch comprises any one of corn starch, wheat starch, rice starch, tapioca starch or sweet potato starch, or a combination of at least two thereof; And / or, the specific steps of the mixing include: Mixing starch and a solvent to obtain a starch emulsion solution, then adding a pH adjuster to adjust the pH, and then adding an oxidant; And / or, the mass volume ratio concentration of the oxidant is 1-20 g / L; And / or, the mass ratio of the starch to the oxidant is 1:(0.002-0.04); And / or, the temperature of the oxidation reaction is 30-50°C; And / or, the temperature of the low temperature pretreatment is 150-350°C; And / or, the low temperature pretreatment time is 6-48h; And / or, the temperature of the high temperature carbonization treatment is 1300-1600°C; And / or, the high temperature carbonization treatment time is 4-10 hours.
9. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: (1) Starch and a solvent are mixed to obtain a starch emulsion solution with a mass concentration of 20-50%, and then a pH adjuster is added to adjust the pH value to 6-9, and then an oxidant with a mass volume ratio concentration of 1-20 g / L is added to carry out an oxidation reaction under stirring conditions to obtain oxidized modified starch; The viscosity of the oxidized modified starch is 6-14 mPa·s, the crystallinity is 8-20%, and the moisture content is ≤11%; the oxidized modified starch contains oxygen-containing functional groups, the oxygen-containing functional groups include carboxyl groups, and the mass content of oxygen-containing functional groups in the oxidized modified starch is 0.05-0.8%; the mass ratio of the starch to the oxidant is 1:(0.002-0.04); the temperature of the oxidation reaction is 30-50°C, and the time is 0.5-3h; (2) In an air atmosphere, the temperature is raised to 150-350°C at a heating rate of 1-5°C / min, and the oxidized modified starch is subjected to a low-temperature pretreatment for 6-48 hours. Then, the temperature is raised to 1300-1600°C at a heating rate of 1-10°C / min in a protective atmosphere for a high-temperature carbonization treatment for 4-10 hours. After the treatment, the temperature is lowered, and the mixture is crushed and sieved to obtain the starch-based hard carbon negative electrode material.
10. A sodium ion battery, characterized in that: The negative electrode plate of the sodium ion battery includes the starch-based hard carbon negative electrode material as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method for starch-based porous hard carbon negative electrode material of lithium ion battery
CN105633380A
Single-crystal high-Ni ternary material precursor, preparation method and preparation method of Single-crystal high-Ni ternary material
CN108298599A
Starch film-forming composition and application thereof in plant soft capsules
CN113121889A
Preparation method and application of hard carbon negative electrode material
CN114702022A
Hard carbon material and preparation method and application thereof
CN115117339A
Cited By
Carbon material and preparation method thereof, silicon-carbon composite material and preparation method thereof, negative electrode and lithium ion battery
CN120709374A
Starch-based hard carbon negative electrode material, preparation method therefor, and sodium ion battery comprising same
WO2026148935A1